Exploring the Factors Influencing Teachers’ Perceptions and Students’ Attitudes in STEM Education Development (Universitas Pendidikan Indonesia, 2026)
The rapid evolution of information and communication technologies, combined with the growing demand for a skilled workforce in science, technology, engineering, and mathematics (STEM) fields, has underscored the importance of STEM education in shaping the future workforce. Despite its critical role, a persistent gap remains between students' academic performance in STEM subjects and their interest in pursuing STEM careers. This study investigates the dynamics of teachers' perceptions and students' attitudes towards STEM education in secondary schools in Indonesia. Using a quantitative approach with a cross-sectional design, this study examines the impact of demographic factors, including gender, educational background, and teaching experience, on teachers' perceptions, as well as how gender and grade level influence students' attitudes towards STEM. The study employed a questionnaire to measure students’ attitudes toward STEM across four dimensions (science, mathematics, technology, and engineering) and teachers’ perceptions across four indicators (STEM understanding, STEM competencies, STEM knowledge, and implementation challenges). The study involved 125 teachers and 447 students, with data analyzed through descriptive statistics, correlation analysis, and ANOVA. Results show that while teachers hold positive perceptions of STEM education, challenges related to resource limitations and the complexity of interdisciplinary teaching remain significant. Students’ attitudes towards STEM varied, with a notable decline in positive attitudes as grade levels increased, especially in mathematics. The findings contribute to the development of more adaptive STEM education policies and practices in Indonesia, providing insights for future educational reforms.